THE EFFECTIVENESS OF MULTI SENSORY INTEGRATION VIA ISLAMIC WAY IN CAPTURING THE INTEREST OF PERVASIVE DEVELOPMENTAL DISORDER AUTISTICS - Wan Norliza Wan Bakar (Jurnal Penyelidikan Sains Sosial, 2019)
Pervasive Developmental Disorder is one of the categories of autism. Autistics suffering from this type of autism show a lack of interest in other people. They display difficulty in communication and exhibit repetitive behaviour. Autistics with the pervasive developmental disorder have a cognitive profile with high skills in spatial organization (Girardot, 2012). The purpose of this study is to spark interest in learning in the autistics suffering from pervasive developmental disorder. Three autistic suffering from pervasive developmental disorder namely from The Special Inclusive Class in a school at Kelantan was selected. A multiple baseline design was implemented. The procedure of the research is divided into three stages. Firstly, a set of Quran verses is played through a cassette to the first pervasive developmental disorder. The Quran Verses of Al Fatihah, Al-Qadr and Al Insyirah are played repeatedly through a cassette player to the first pervasive developmental disorder. After he reaches the state of stability then the multi-sensory integration was given by the researcher to the pervasive developmental disorder.it is by giving a toy car to him and made him play to and fro. After a few minutes he reaches the state of stability. Secondly, the set of Quran verses is again applied to the second pervasive developmental disorder. After half an hour he reaches the state of stability. Then the researcher use multi-sensory integration approach by giving him a toy car and made him play to and fro. After a few minutes he reaches the state of stability. Thirdly the set of Quran verses is again applied to the second pervasive developmental disorder. After half an hour he reaches the state of stability. Then the researcher use multi-sensory integration approach by giving him a toy car and made him play to and fro. The results indicated that by using the Quran verses the pervasive developmental disorder autistic became calm and this enabled him to speak and to play cheerfully. Future research should be implemented on the pervasive developmental disorder’s interest that will lead to his career path.